2022
DOI: 10.1021/jasms.2c00204
|View full text |Cite
|
Sign up to set email alerts
|

A UPLC-MS/MS Method for Plasma Biological Monitoring of Nirmatrelvir and Ritonavir in the Context of SARS-CoV-2 Infection and Application to a Case

Abstract: Nirmatrelvir/ritonavir association has been authorized for conditional use in the treatment of COVID-19, especially in solid-organ transplant recipients who did not respond to vaccine and are still at high risk of severe disease. This combination remains at risk of drug interactions with immunosuppressants, so monitoring drug levels seems necessary. After a simple protein precipitation of plasma sample, analytes were analyzed using an ultrahigh performance liquid chromatography system coupled with tandem mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In one liver transplant recipient who had recently undergone kidney transplantation, Guyon et al. ( 17 ) discontinued all immunosuppressants. Patients resumed taking tacrolimus either 12 h after the last dose of NR at 100% of the baseline dose ( 17 ), on day 7 (day 1 being the day of NR initiation) at 100% ( 15 ), or 3 days (2–5 days) after the completion of NR at 82% (interquartile range (IQR), 71–100) of their baseline dose ( 13 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In one liver transplant recipient who had recently undergone kidney transplantation, Guyon et al. ( 17 ) discontinued all immunosuppressants. Patients resumed taking tacrolimus either 12 h after the last dose of NR at 100% of the baseline dose ( 17 ), on day 7 (day 1 being the day of NR initiation) at 100% ( 15 ), or 3 days (2–5 days) after the completion of NR at 82% (interquartile range (IQR), 71–100) of their baseline dose ( 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…( 14 ) reported that three patients experienced supratherapeutic levels (> 20 ng/ml), and Guyon et al. ( 17 ) reported a patient with a tacrolimus trough level of > 111 ng/ml.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations